On the Ubiquity of Magnetic Reconnection Inside Flux Transfer Event‐Like Structures at the Earth's Magnetopause. Issue 6 (16th March 2020) - Fargette, N.; Lavraud, B.; Øieroset, M.; Phan, T. D.; Toledo‐Redondo, S.; Kieokaew, R.; Jacquey, C.; Fuselier, S. A.; Trattner, K. J.; Petrinec, S.; Hasegawa, H.; Garnier, P.; et al.
Abstract: Flux transfer events (FTEs) are transient phenomena frequently observed at the Earth's magnetopause. Their usual interpretation is a flux rope moving away from the reconnection region. However, the Magnetospheric Multiscale Mission revealed that magnetic reconnection sometimes occurs inside these structures, questioning their flux rope configuration. Here we investigate 229 FTE‐type structures and find reconnection signatures inside 19% of them. We analyze their large‐scale magnetic topology using electron heat flux and find that it is significantly different across the FTE reconnecting current sheets, demonstrating that they are constituted of two magnetically disconnected structures. We also find that the interplanetary magnetic field (IMF) associated with reconnecting FTEs presents a strong B y component. We discuss several formation mechanisms to explain these observations. In particular, the maximum magnetic shear model predicts that for large IMF B y, two spatially distinct X lines coexist at the magnetopause. They can generate separate magnetic flux tubes that may become interlaced. Plain Language Summary: The solar wind and the Earth's magnetosphere are two gigantic magnetic structures that collide constantly over our heads, in the near‐space environment. At the boundary of their interaction (the magnetopause), the fundamental process of magnetic reconnection can occur. It is there that dynamic magnetic structures called "flux transfer events" are formed. They travel fast along the magnetopause and transport a lot of energy, from the solar wind into the magnetosphere. These structures are yet not well understood, as underlined by the recent observations made by the Magnetospheric Multiscale Mission (MMS), launched in 2015 by National Aeronautics and Space Administration. The four‐spacecraft mission, specifically designed to study the physics happening at the magnetopause, is capable of measuring right into these magnetic structures, collecting data on their particles and magnetic field properties. When analyzing MMS data, we found that 19% of the flux transfer events were not constituted of one, but two structures with very different properties. These dual magnetic structures tend to appear when the solar wind's magnetic field is oriented mainly toward the east or the west. From these observations and based on existing models of the magnetopause, we propose a scenario that allows such dual structures to form as interlaced magnetic tubes. Key Points: Nineteen percent of FTE‐type structures observed by MMS during Phases 1A and 1B present signatures of magnetic reconnection in their core They seem to be formed by two magnetically disconnected interlaced flux tubes and are typically observed for large IMF B y Several formation models are discussed, including a bifurcated X line scenario that results from the maximum shear angle model